ELEMENTS OF NANOSTRUCTURE PHYSICS FOR STUDENTS AND PUPILS - Ivanova, Marina; Puchkov, Nikolai; Solovyev, Vladimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Physics of nanostructures is the scientific basis of modern nanotechnologies that use the special properties of small particles with a size of about 1–100 nm, making it possible to design various novel materials with unique physical properties. Today a training of future professionals to work in this technological area is very important. Moreover, this training is desirable not only at universities, but also at schools in order to introduce nanotechnologies to the young generation. The purpose of this work is an analysis of possibilities for familiarization of students and pupils in Pskov (Russia) with the elements of nanostructure physics, as well as subsequent development and testing of didactic materials on this topic. As a part of this work, a study of the current state of nanostructure physics has been conducted. As a result, the authors have developed overview lectures on modern nanotechnology and educational nanotechnological laboratory experiments for students and pupils.